The role of carbon atoms of supported iron carbides in Fischer–Tropsch synthesis. Issue 3 (22nd January 2015) - Ordomsky, V. V.; Legras, B.; Cheng, K.; Paul, S.; Khodakov, A. Y.
Abstract : High reactivity of iron carbides enhances the Fischer–Tropsch reaction rate on supported iron catalysts. Carbon atoms in iron carbide are involved in the initiation of chain growth in Fischer–Tropsch synthesis. Abstract : High reactivity of iron carbides enhances the Fischer–Tropsch reaction rate on supported iron catalysts. Highly dispersed carbide is easily hydrogenated to methane in a hydrogen atmosphere with subsequent regeneration in the presence of CO. Carbon atoms in iron carbide are involved in the initiation of chain growth in Fischer–Tropsch synthesis.